Irregular meal pattern-effects on energy expenditure, metabolism and appetite regulation: a randomized controlled trial in healthy normal-weight women - Alhussain, Maha H; MacDonald, Ian A.; Taylor, Moira A. (American Society for Nutrition, 2016)
Background: Obesity is increasing in parallel with greater all-day food availability. The latter may promote meal irregularity, dysregulation of the energy balance, and poor metabolic health. Objective: We investigated the effect of meal irregularity on the thermic effect of food (TEF), lipid concentrations, carbohydrate metabolism, subjective appetite, and gut hormones in healthy women. Design: Eleven normal-weight women (18–40 y of age) were recruited in a randomized crossover trial with two 14-d isoenergetic diet periods (identical foods provided and free living) that were separated by a 14-d habitual diet washout period. In period 1, participants followed a regular meal pattern (6 meals/d) or an irregular meal pattern (3–9 meals/d), and in period 2, the alternative meal pattern was followed. Before and after each period, when participants were fasting and for 3 h after intake of a test drink, measurements were taken of energy expenditure, circulating glucose, lipids (fasting only), insulin, glucagon-like peptide 1 (GLP-1), peptide YY (PYY), and ghrelin. An ad libitum test meal was offered. Subjective appetite ratings were assessed while fasting, after the test drink, after the ad libitum meal, and during the intervention. Continuous interstitial glucose monitoring was undertaken for 3 consecutive days during each intervention, and the ambulatory activity pattern was recorded (ambulatory energy expenditure estimation). Results: Regularity was associated with a greater TEF (P , 0.05) and a lower incremental area under the curve (iAUC) for glucose after intake of the test drink (over 3 h) and, for some identical meals, during the 2 interventions (over 90 min) (day 7: after breakfast; day 9: after lunch and dinner). There was no difference between treatments for the test-drink gut hormone response. A time effect was noted for fasting GLP-1, fasting PYY, PYY responses, and hunger-rating responses to the test drink (P ˂ 0.05). Lower hunger and higher fullness ratings were seen premeal and postmeal during the regular period while subjects were free living. Conclusion: Meal regularity appears to be associated with greater TEF and lower glucose responses, which may favor weight management and metabolic health. This trial was registered at clinical trials.gov as NCT02052076.